MODERN ASPECTS OF TREATMENT OF GENITAL HERPES INFECTION - I. O. Makarov; T. V. Ovsyannikova; I. A. Kulikov (Акушерство, гинекология и репродукция)
This article describes the present views on the treatment of genital herpes infection. Examined topical therapies HSV.